Peran Pendidikan Agama Kristen Dalam Meningkatkan Kemandirian Peserta Didik Di Era Kurikulum Merdeka - Elfin Warnius Waruwu; Enisabe Waruwu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
PAK is an education that focuses on teaching Christian values and doctrines to students. The aim is to help students understand the teachings of Christianity, deepen their relationship with God, and form good character and morals. However, the fact is that some students do not understand Christian values. Students often only understand Christianity theoretically without being able to apply it in everyday life. This can hinder the development of student independence. In this study or study the authors used qualitative research methodologies and literature studies. The results of the study show that PAK can make a positive contribution to the development of student independence. Through teaching Christian values that encourage self-awareness and responsibility, students can acquire skills and attitudes that support independence, such as the ability to make decisions, be independent in learning, and play an active role in society. In the context of an independent curriculum, students can be integrated into the curriculum to support the development of student independence.